2005
DOI: 10.2337/diabetes.54.1.275
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Insulin Secretion, Peripheral and Hepatic Insulin Action, and Intracellular Glucose Partitioning in Young and Old Danish Twins

Abstract: The etiology of type 2 diabetes is multifactorial, including genetic as well as pre-and postnatal factors that influence several different defects of glucose homeostasis, primarily in muscle, ␤-cells, and liver. In the present twin study, we report heritability estimates (h 2 ) for measures of insulin secretion, insulin resistance, hepatic glucose production (HGP), and intracellular glucose partitioning using gold standard methods (euglycemic-hyperinsulinemic clamp technique, tritiated glucose infusion, indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
1
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(151 citation statements)
references
References 34 publications
(39 reference statements)
7
136
1
3
Order By: Relevance
“…These findings cannot simply be attributed to a restricted range of BMI or ISI values in this healthy sample, since our heritability estimates of BMI and insulin sensitivity are very comparable to previous estimates [11,12,33]. Furthermore, the partial independence of genetic factors influencing beta cell function from those influencing BMI is congruent with the outcome of previous genome-wide association (GWA) studies addressing the genetic risk of diabetes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings cannot simply be attributed to a restricted range of BMI or ISI values in this healthy sample, since our heritability estimates of BMI and insulin sensitivity are very comparable to previous estimates [11,12,33]. Furthermore, the partial independence of genetic factors influencing beta cell function from those influencing BMI is congruent with the outcome of previous genome-wide association (GWA) studies addressing the genetic risk of diabetes.…”
Section: Discussionsupporting
confidence: 86%
“…Twin [2][3][4][5] and family studies [6][7][8][9][10] support the notion that people who develop type 2 diabetes have a strong genetic predisposition, which may be partly conveyed through genetic effects on insulin resistance. Two twin studies, for instance, showed a significant genetic contribution to insulin sensitivity, assessed by euglycaemic-hyperinsulinaemic clamp with heritability estimates of 37% and 55% [11,12]. Notwithstanding the importance of insulin sensitivity, genetic effects on beta cell function are likely to play a major role in the development of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high number of statistically highly associated variants discovered in the last few years, the explained proportion of the interindividual variation reported in Inter99 for the combination of all 33 validated type 2 diabetes and/or fasting plasma glucose gene variants is only 5.8% for fasting plasma glucose and 4.2% to 5.7% for different estimates of glucose-stimulated insulin release in non-diabetic Danish people (data not shown). These numbers should be interpreted in relation to heritability estimates of 30% to 40% and 60% to 80% for fasting glucose and first-phase insulin release, respectively [32], indicating that 15% to 20% and 5% to 10%, respectively, of the genetic contribution to these traits has been accounted for. These estimates imply that a major part of the genetic contribution to these quantitative traits is yet to be unravelled.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of glucose disposal, its partitioning into oxidation and nonoxidative glucose metabolism as well as fat oxidation were calculated as previously reported and expressed as mg (kg lean body mass) −1 min −1 [23]. Muscle biopsies were obtained from the vastus lateralis muscle under local anaesthesia during both basal and insulin-stimulated states.…”
Section: Clinical Examination and Muscle Biopsies In Twinsmentioning
confidence: 99%